Obesity-Related Dyslipidemia in Domestic Cats: A Comparative Analysis of Lipid Profile Alterations - Dal’Agnol Lara, Gabriela; Lordello Gulin, Verônica; Serighelli-Júnior, Gilberto; Hanna de Pauli Flaksberg, Ester; Jun Hironaka Nakao, César; Tavares de Abreu, Gabriellye; Locatelli Dittrich, Rosangela (Archives of Veterinary Science, 2025)
Feline obesity is a prevalent disorder that predisposes cats to metabolic diseases, but comprehensive data on its specific effects on serum lipid profiles are lacking. This study aimed to establish reference intervals for HDL cholesterol and a lipid profile in healthy lean cats; characterized serum concentrations of total cholesterol, HDL, VLDL, LDL, and triglycerides, and to characterize alterations across body condition scores, age groups, and between sexes. In a prospective cross-sectional study of eighty-five client-owned cats (25 lean, 60 overweight/obese), body condition was assessed using body weight and a 9-point BCS system. Biochemical analyses were performed using a Mindray® BS200 automated analyzer. Results established an HDL reference interval of 39.1–163.9 mg/dL for lean cats. Obesity was linked to a distinct dyslipidemia, characterized by a pronounced 58% increase in triglycerides and rising VLDL. Interestingly, while HDL increased with obesity, total cholesterol was up to 13% higher in overweight versus obese cats, indicating a complex metabolic relationship. A significant finding was that 71.2% of young adult cats were already above ideal BCS, with the highest obesity rate (40%) in mature adults. A notable sex disparity was observed, with male cats showing a greater tendency toward higher adiposity.